Pola Pendidikan Karakter di SMP Ibrahimy 2 Sukorejo - Moh. Hafid; Aisyah Deslantari Rhomadania (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Character education at the junior high school (SMP) level is very important because adolescence is a transition period from children to adults, where the cultivation of moral and ethical values is very crucial. The implementation of character education in Indonesian schools still faces many challenges. In some schools, character education has not been implemented optimally. Therefore, this research aims to analyze the pattern of character education at SMP Ibrahimy 2 Sukorejo. This research uses a qualitative descriptive research method using teacher and student interviews for data collection. Based on the results of research and analysis conducted by SMP Ibrahimy 2 Sukorejo, it has implemented holistic character education through various integrated approaches. The integration of character education into subjects and extracurricular activities has helped students understand moral and ethical values contextually and relevant to their daily lives. Apart from that, special programs such as mentoring and social activities also contribute to the formation of student character. A school culture that prioritizes values such as honesty, responsibility, cooperation and respect for others has also created a learning environment that is conducive to the growth of students' character